Hurting and healing in therapeutic environments: how can we understand the role of the relational context? - Clarke, Simon P.; Clarke, Jenelle M.; Brown, Ruth; Middleton, Hugh (Taylor & Francis, 2016)
It has long been recognized that relationships are key to good mental health service delivery and yet the quality of the relational context remains poorly understood. This article brings together three studies that utilize very different methodologies to explore the various ways in which a process of therapeutic change can be aided or prevented by relational factors. All three studies took place within the context of therapeutic communities. The first study uses narrative ethnography and interaction ritual theory to explain how the mechanisms of everyday encounters in two therapeutic communities transform negative feeling into a sense of belonging and positive emotions such as confidence. The second study uses grounded theory to explore how the relational setting and the altered context of the researcher in a therapeutic faith community environment induces either a positive or negative quality of relationships. The final study uses a novel autoethnographic methodology to inform understanding of the relational experience of mental health treatment by comparing and contrasting multiple perspectives of different treatment environments. The paper concludes by identifying the expression and containment of affect in a congruent environment, belonging and hope, and fluid hierarchies of relational structures as key aspects of the relational context informing change.